Influence of age of child on differences in life satisfaction of males and females: A comparative study among East Asian countries - Eiji Yamamura; Antonio Rodriguez Andres (Institute for Advanced Development Studies (INESAD), 2012)
Using individual-level data for China,South Korea, and Japan for2006, this research examines how life satisfaction for married males and femalesin East Asian countries isinfluenced bythe age of theirchildren. Our results show that the life satisfaction of males is barely affected by a child of the relationship, whereas the life satisfaction of females with a young child is lower than that of females who do not have a child. This result holds for countries at different development stages. There is also a gender differential regarding the effect of young children on life satisfaction. Furthermore, the more developed the country, the greater this difference becomes.
Keywords: D19; J13; J16; 330; Life satisfaction; child; East Asian countries; Ordered probit